Interpretation of youth from the thinking of Badiuzzaman said Nursi - Gamon, Alizaman Dumangcag; U Tun Aung, Maulana Akbar Shah; Abdul Razak, Mohd Abbas; Ali, Mohammed Farid (the International Islamic University Malaysia, 2020)
Today’s youth are the beacons of light and the leaders of tomorrow. Thus, as responsible careers and educators, the elders need to invest more of their time in nurturing young people to become more attuned with their Islamic identity, helping them to become both intelligent and pious. As aspiring minds, it is believed that the answer to forming a good society lies in education. When individuals and the Ummah at large follow education, the community will be able to achieve stability, safety, and happiness in the face of controversy and opposition. This claim is followed by the thought of Bediuzzaman Said Nursi as he said: "We Muslims, who are students of the Qur’an, follow proof; we approach the truths of belief through reason, though, and our hearts." Bediuzzaman is the all-inclusive guide for youth for any generation. This paper highlights the importance of thinking and approach of Bediuzzaman Said Nursi on ethics and morality, as they are depicted in his book “Risel-a-Noor.” Ethics which brings a lot of benefits to people who practice them, such as be a better person, and also be a factor to attract non-Muslims to the fold of Islam, when the behaviour of the Muslims reflects the true teachings of the Qur’an and Sunnah. Among the ethical values in Islam, moderation, fairness and justice in the way of thinking and actions are highly recommended in the Qur’an. In the following quote, Allah SWT draws the attention of the Muslims to moderate in all their affairs: “And thus we have made you a just community that you will be witnesses over the people and the Messenger will be a witness over you.” In the present study the researchers would like to analyze the ideas of Said Nursi with regard to youth and the ideal activities they should be involved in. Besides that, the researchers would like to venture into his concept on how to produce good Muslim youth who can be great future leaders. Being qualitative in nature, this research will use the textual and content analysis method in analyzing the relevant data.